Shakespeare by the Sea Festival (19th Annual) - Carr, Alison (2011)
Black and White Reads Denmark. Illyria. Baker Street. Pigeon Inlet? This Summer, let us take you to another world - in your own backyard. Kelly Russell's Tunes and Tales, Above and Below, Twelfth Night, The Curious Case in the Colony: A Sherlock Holmes Adventure, Hamlet.